Improved Genome Sequence of Wild Emmer Wheat Zavitan with the Aid of Optical Maps. Issue 3 (1st March 2019) - Zhu, Tingting; Wang, Le; Rodriguez, Juan C; Deal, Karin R; Avni, Raz; Distelfeld, Assaf; McGuire, Patrick E; Dvorak, Jan; Luo, Ming-Cheng
Abstract: Wild emmer ( Triticum turgidum ssp. dicoccoides ) is the progenitor of all modern cultivated tetraploid wheat. Its genome is large (> 10 Gb) and contains over 80% repeated sequences. The successful whole-genome-shotgun assembly of the wild emmer (accession Zavitan) genome sequence (WEW_v1.0) was an important milestone for wheat genomics. In an effort to improve this assembly, an optical map of accession Zavitan was constructed using Bionano Direct Label and Stain (DLS) technology. The map spanned 10.4 Gb. This map and another map produced earlier by us with the Bionano's Nick Label Repair and Stain (NLRS) technology were used to improve the current wild emmer assembly. The WEW_v1.0 assembly consisted of 151, 912 scaffolds. Of them, 3, 102 could be confidently aligned on the optical maps. Forty-seven were chimeric. They were disjoined and new scaffolds were assembled with the aid of the optical maps. The total number of scaffolds was reduced from 151, 912 to 149, 252 and N50 increased from 6.96 Mb to 72.63 Mb. Of the 149, 252 scaffolds, 485 scaffolds, which accounted for 97% of the total genome length, were aligned and oriented on genetic maps, and new WEW_v2.0 pseudomolecules were constructed. The new pseudomolecules included 333 scaffolds (68.51 Mb) which were originally unassigned, 226 scaffolds (554.84 Mb) were placed into new locations, and 332 scaffolds (394.83 Mb) were re-oriented. The improved wild emmer genome assembly is an important resource for understanding genomic modification that occurred by domestication.